Factores que inciden en el desarrollo comunicativo de los niños y niñas del Centro Infantil “Fantasía de las Américas” de la ciudad de Medellín. - Montiel Castro, Luz Eirene; Cifuentes Villegas, Luisa Fernanda; Serna Cardona, María Camila (Corporación Universitaria Minuto de Dios, 2018)
El presente trabajo de investigación tiene como objetivo determinar los factores externos que inciden en la comunicación de los niños del Centro Infantil “Fantasía de las Américas” en la ciudad de Medellín. Desde las teorías psicopedagógicas sobre el desarrollo del lenguaje, los niños de esta institución presentan falencias que pueden ser causadas por factores externos como la familia y situación socioeconómica y la falta de actividades pedagógicas alternativas en la institución educativa... Teniendo en cuenta este panorama investigativo, se ejecuta una propuesta de intervención desde la musicoterapia definida como la estrategia más adecuada y fácil de implementar para los docentes del centro infantil.

This research tries to determine the external factors that affect the communication of children of the Fantasia de las Americas Children's Center in the city of Medellin. Children from this educative center are demonstrating some communicative weakness which are studied by psychologists, they could be caused by external factors like those of family, economics ones and the necessity of pedagogical external activities. The children who attend this center belong to the lower strata of the city and have social particularities from economic and cultural situation affecting the development of the articulated language communication. To recognize this problem, an investigation is carried out with the qualitative approach and the use of techniques such as interviews, surveys and observation with the educative community. as a result, it was found that, first, there are visible difficulties in the development of 5 language and the way they communicate with other children. second, there is a clear link between these difficulties and parenting communication with them. And third, the children center does not have the resources or strategies that can provide tools for children to improve their communication. Taking into account the conclusions, a proposal of a pedagogical work was executed and the music therapy was defined as the most appropriate and easy to develop by teachers of the infantile center; This project was organized with seven activities and it was successful because it made possible to bring a significant change in the articulated language and the communication of the children who participated on it
Determinar los principales factores que inciden en el desarrollo de la comunicación en niños de Conquistadores 1 del Centro “Infantil Fantasía de las Américas” en el barrio Popular 2 de la ciudad de Medellín.
Keywords: Desarrollo de la Comunicación; Lenguaje articulado; Musicoterapia; Enfoque cualitativo; Desarrollo del lenguaje; Musicoterapia; Psicopedagogía